Co-existence of magnetic phases in two-dimensional MXene. (June 2020) - Iqbal, Mehroz; Fatheema, Jameela; Noor, Qandeel; Rani, Malika; Mumtaz, Muhammad; Zheng, Ren-Kui; Khan, Saleem Ayaz; Rizwan, Syed
Abstract: This study reports first synthesis of MXene-derived co-existing magnetic phases. New family of two-dimensional (2D) materials such as Ti3 C2 namely MXene, having transition metal forming hexagonal structure with carbon atoms have attracted tremendous interest now a days. We have reported structural, optical and magnetic properties of un-doped and La-doped Ti3 C2 Tx MXene, synthesized using co-precipitation method. The lattice parameter (LP) calculated for La-MXene are a = 5.36 Å, c = 18.3 Å which are slightly different from the parent un-doped MXene (a = 5.35 Å, c = 19.2 Å), calculated from X-ray diffraction data. The doping of La +3 ions shrinks Ti3 C2 Tx layers perpendicular to the planes. The band gap for MXene is calculated to be 1.06 eV which is increased to 1.44 eV after doping of La +3 ion that shows its good semiconducting nature. The experimental results and density functional theory (DFT) calculations for magnetic properties of both the samples have been presented and discussed, indicating the co-existence of ferromagnetic-antiferromagnetic phases. The results presented here are novel and is first report on co-existence of magnetic properties of 2D carbides for potential applications in two-dimensional spintronics. Graphical abstract: Schematic representation of La embedded into the MXene sheets. Image 1 Highlights: First synthesis of MXene-derived multiferroic phases containing ferromagnetic and antiferromagnetic phases simultaneously. MXene and rare-earth lanthanum doped MXene studied and comparison of optical and magnetic properties of both systems. Density function theory calculations to study magnetic behavior of pristine and doped MXene structures. Our results is the first experimental and theoretical report on bi-magnetic nature of undoped and doped MXene. Indication for the possibility of two-dimensional carbides-based spintronics for data storage applications.